Relative Contributions of the Speed Characteristic and Other Possible Ecological Factors in Synchronization to a Visual Beat Consisting of Periodically Moving Stimuli - Huang, Yingyu; Gu, Li; Yang, Junkai; Zhong, Shengqi; Wu, Xiang (Frontiers in Psychology, 2018)
Daily music experience involves synchronizing movements in time with a perceived periodic beat. Contrary to the auditory-specific view of beat synchronization, synchronization to a visual beat composed of a periodically bouncing ball has been shown to be not less stable than synchronization to auditory beats. The ecological relevance of periodically moving visual stimuli is considered to be essential for such synchronization improvement. However, multiple factors could be associated with the ecological relevance and the relative contributions of the ecological factors to the synchronization improvement remain unclear. The present study investigated whether ecological factors other than a proposed critical factor, i.e., the speed characteristic, are required to account for the synchronization improvement of the bouncing ball. A periodically contracting ring that had the same speed characteristic as the periodically bouncing ball but lacked other possible ecological factors of the ball was designed. The results showed that synchronization was more stable for the bouncing ball than for the contracting ring, and this stability difference was larger in the difficult 300-ms than in the comfortable 600-ms inter-beat interval tapping condition. The finding suggests that ecological factors other than the speed characteristic are required to explain the synchronization improvement of periodically moving visual stimuli, particularly in difficult tapping conditions.